How to be a good tech lead - Fournier, Camille (O'Reilly, 2018)
In this chapter from The Manager's Path, you'll learn the biggest trick of being a good tech lead: the willingness to step away from the code and figure out how to balance your technical commitments with the work the whole team needs. From mentoring interns to working with senior staff, you'll get actionable advice for approaching various obstacles in your path. Link to proposal.